2001
DOI: 10.1111/j.1151-2916.2001.tb00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure in Silicon Nitride Containing β‐Phase Seeding: III, Grain Growth and Coalescence

Abstract: The mechanical properties of Si 3 N 4 materials depend mainly on the microstructure, which originates during the densification process. The microscopic evidence indicates that ␤-Si 3 N 4 seeds incorporated in the starting powders play an important role in microstructural development, especially in the heterogeneous grain growth of ␤-Si 3 N 4 grains during sintering. The growth of ␤-grains is initiated from the ␤-seeds, resulting in a core/shell microstructure. The presence of Moiré fringes and dislocations is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…2 O 3 dissolved into the host β-Si 3 N 4 to afford metastable solid solution or the present high-temperature sintering at 1950 • C allowed physical incorporation of the Mg-Gd-Si-O-N liquid into the host β-Si 3 N 4 as previously suggested for the liquid phase sintered β-Si 3 N 4 -based ceramics 7,8,13,14. …”
supporting
confidence: 64%
See 2 more Smart Citations
“…2 O 3 dissolved into the host β-Si 3 N 4 to afford metastable solid solution or the present high-temperature sintering at 1950 • C allowed physical incorporation of the Mg-Gd-Si-O-N liquid into the host β-Si 3 N 4 as previously suggested for the liquid phase sintered β-Si 3 N 4 -based ceramics 7,8,13,14. …”
supporting
confidence: 64%
“…11,12 Despite the short sintering period, glassy precipitates with diameters less than 100 nm were observed at the boundary between the core originating from the β-Si 3 N 4 seed and the shell epitaxially grown onto the β-Si 3 N 4 seed via the solution-precipitation of some α-phase particles initially located around the β-Si 3 N 4 seed. 13 It was suggested that the glassy inclusions were trapped by rapid β-Si 3 N 4 grain growth during the initial stage of the α-⇀ β-Si 3 N 4 phase transformation via the solution-reprecipitation through the liquid phase formed in situ or segregated and remained after the increase in sintering temperature and time. 13 Yokota et al 14 also suggested that a portion of the liquid phase was trapped by rapid β-Si 3 N 4 growth during the α-⇀ β-Si 3 N 4 phase transformation and remained as intragranular nanoprecipitates after homogenization: either hexagonal or spherical precipitates with a diameter of 10-30 nm were observed within the β-Si 3 N 4 grains of Si 3 N 4 -Yb 2 O 3 (10 wt%)-ZrO 2 (2 wt%) ceramics sintered at 1900 • C for 8 h under N 2 pressure at 0.9 MPa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Figure 12(a) shows the BF/TEM micrograph in the middle of the large, elongated grain. An APB occurred when the atoms sheared through a displacement and formed an y ABBA y arrangement, which offers possible evidence of grain coalescence during sintering.…”
Section: (5) Anisotropic Grain Growth By Coalescencementioning
confidence: 99%
“…An APB occurred when the atoms sheared through a displacement and formed an y ABBA y arrangement, which offers possible evidence of grain coalescence during sintering. 42 Figure 12(a) shows the BF/TEM micrograph in the middle of the large, elongated grain. The figure reveals that a periodically arranged lattice fringe (subgrain X) is involved in the large, elongated grain.…”
Section: (5) Anisotropic Grain Growth By Coalescencementioning
confidence: 99%